A Study on the Novels of Arundhati Roy: Exploring Arundhati Roy's Impact on Contemporary Social-Political Discourse (Journal of Advances and Scholarly Researches in Allied Education, 2014)
ArundhatiRoy is one of the few Indian English writers actively interested incontemporary social – political issues which is amply evidenced in a number ofarticles, interviews and books she wrote on various topics in recent years.Mrs. Roy has authored such thought provoking works as “Confronting Empire”,“The Algebra of Infinite Justice” (2002). An internationally acclaimed essaycalling upon the world not to use violence against innocent people inAfghanistan, and “War is Peace” (2002), another powerful essay. Her books like.“The Threat of Nuclear Weapons”. ‘The promotion of Equal Rights’.